A Study of Epiphytic and Epipelic Algae in Al-Dora Site/Tigris River in Bagdad Province- Iraq (Baghdad Science Journal, 2025)
There is a scarcity of data regarding algal flora of Tigris River in the territory of Baghdad. The present study deals with Tigris River in Al-Dora site in Baghdad province from November 2014 to June 2015 in order to shed light on its epiphytic Algae on (Phragmites australis) and epipelic algae. An amount of 183 and 154 species of epiphytic and epipelic algae are identified respectfully. The Bacillariophyceae (diatoms) are the dominant algal group followed by Cyanophyceae and Chlorophyceae. Moreover, 90 species are shared between two groups of algae (epiphytic and epipelic) and identified at the study site. Additionally, the seasonal variations and diversity of algal species are noticed. The highest number of epiphytic algae is 772.05 x 104 (cell/gm) in winter and the lowest number is 161.13 x 104 (cell/gm) in Summer; where as the highest number of epipelic algae is 20.07 x 104 (cell/ cm²) in Winter and the lowest number is 6.53 x 104 (cell/ cm²) in Summer.